Comparison of survival among neoadjuvant chemoradiation responders, non-responders and patients receiving primary resection for locally advanced oesophageal squamous cell carcinoma: does neoadjuvant chemoradiation benefit all? - Hsu, Po-Kuei (Oxford University Press, 2013)
OBJECTIVES: While neoadjuvant chemoradiation followed by surgery has been shown to improve the survival of patients with locally advanced oesophageal cancer, it is not known whether neoadjuvant chemoradiation has a beneficial or harmful effect on the non-responders. We aimed to compare the outcomes among neoadjuvant chemoradiation responders, non-responders and patients receiving primary oesophagectomies for resectable locally advanced oesophageal squamous cell carcinoma. METHODS: Eighty-four non-T1–2N0 oesophageal squamous cell carcinoma patients were included. Thirty-eight patients received primary resection and 46 patients received neoadjuvant chemoradiation. The overall survival of chemoradiation responders (<50% residual tumour), non-responders (>50% residual tumour and those who shifted to definitive chemoradiation instead of surgery due to tumour progression) and patients receiving primary resection were compared. Clinical parameters were also compared between responders and non-responders. RESULTS: There was no overall difference in survival between neoadjuvant chemoradiation and primary resection groups (2-year overall survival rates: 45.6 vs 54.3%, P = 0.442). In patients receiving neoadjuvant chemoradiation followed by surgery, pathological responders had significantly higher 2-year overall survival rates than non-responders (64.5 vs 38.9%, P = 0.043). While the pathological responders had the highest survival rate, clinicopathological non-responders (pathological non-responders and patients with tumour progression during the neoadjuvant chemoradiation period) demonstrated significantly worse outcomes than those receiving primary resection (32.0 vs 54.3%, P = 0.036). However, none of the clinical parameters, including blood profiles, images and baseline tumour characteristics, predicted the response to chemoradiation before treatment. CONCLUSIONS: Neoadjuvant chemoradiation non-responders demonstrated no benefit and an even worse outcome compared with those receiving primary resection for locally advanced oesophageal squamous cell carcinoma. However, no significant clinical parameters could be implemented in the clinics to predict the response to neoadjuvant chemoradiation before treatment.